(untitled) (Italian Journal of Public Health, 2010)
Background: The presence of Giardia was investigated along the Oreto river between January 2008 and May 2009 with the aim of understanding the source of contamination by molecular typing of cysts. Methods: A total of 38 water samples (10 collected from the river mouth, 24 from the whole Oreto basin and 4 sewage samples from the Monreale treatment plant) were processed. In addition, 22 faecal samples of livestock living close to the Oreto area, were analyzed. The presence of Giardia was determined by immunofluorescence assay and their genetic characterization was achieved by a nested PCR assay targeting the triosephosphate isomerase gene. Results: All water samples from the river mouth were positive for Giardia, even if the concentration of cysts fluctuated considerably among sampling occasions. Our investigation showed that the Vadduneddu and Altofonte torrents, two influents of the river, were the principal sources of contamination. Moreover, the genotypes of Vadduneddu torrent were the same as those detected in human wastewater taken from the activated sludge plant of Monreale city. Assemblages A and B were found in water samples with a predominance of Assemblage A, subtype AII. Assemblage E was only found in a single calf isolate. Conclusions: The data show that the high cyst counts regularly detected in the Oreto river are due to contamination with wastewater of human origin. This finding is relevant for public health, particularly because river water is used for agricultural purposes.